2021
DOI: 10.3390/cimb43030109
|View full text |Cite
|
Sign up to set email alerts
|

CgMFS1, a Major Facilitator Superfamily Transporter, Is Required for Sugar Transport, Oxidative Stress Resistance, and Pathogenicity of Colletotrichum gloeosporioides from Hevea brasiliensis

Abstract: Colletotrichum gloeosporioides is the main causal agent of anthracnose in various plant species. Determining the molecular mechanisms underlying the pathogenicity and fungicide resistance of C. gloeosporioides could help build new strategies for disease control. The major facilitator superfamily (MFS) has multiple roles in the transport of a diverse range of substrates. In the present study, an MFS protein CgMFS1 was characterized in C. gloeosporioides. This protein contains seven transmembrane domains, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The results revealed that the tolerance of ∆CgHOS2 to oxidative, salt, and cell wall inhibitor stress was decreased compared with that of the WT. In addition, the expression levels of a series of MFS and ABC transporters, which are related to stress tolerance (Reddy et al 2012;Liu et al 2021), were decreased in ∆CgHOS2, and the expression of many cell wall synthesis-related enzymes was also decreased in the mutant. The decrease in the stress tolerance of ∆CgHOS2 might partly result from the repression of these genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the tolerance of ∆CgHOS2 to oxidative, salt, and cell wall inhibitor stress was decreased compared with that of the WT. In addition, the expression levels of a series of MFS and ABC transporters, which are related to stress tolerance (Reddy et al 2012;Liu et al 2021), were decreased in ∆CgHOS2, and the expression of many cell wall synthesis-related enzymes was also decreased in the mutant. The decrease in the stress tolerance of ∆CgHOS2 might partly result from the repression of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…The gene complementation and CgHOS2-sGFP expression plasmids were linearized before protoplast transformation. Protoplast preparation and transformation were carried out as described previously (Liu et al 2021). At 3-4 days after transformation, the transformants resistant to chlorimuron ethyl or hygromycin B were selected for further PCR detection.…”
Section: Construction Of Cghos2 Knockout Complementation and Cghos2-s...mentioning
confidence: 99%
“…Vegetative growth of C. gloeosporioides was examined by culturing the strains on minimal medium. The stress tolerance of the strains was estimated according to our previous work (Liu, Wang, et al, 2021). The chemicals 10 and 50 mM H 2 O 2 , 0.7 M NaCl, 1 M sorbitol, 0.25 mg/L Congo red, 0.1 μg/ml fludioxonil, 10 μg/ml iprodione, 0.2 μg/ml tebuconazole, and 2.5 μg/ml TriadiMefon were used to simulate stresses.…”
Section: Methodsmentioning
confidence: 99%
“…In plant pathogens, transporters play an essential role in protection against plant defence mechanisms. One of the major classes of transporter is the major facilitator superfamily (MFS) transporter ( CgMfs1 ), which is very similar to hexose transporters required for sugar transport, resistance to oxidative stress, and the pathogenicity of C. gloeosporioides (Liu et al, 2021). C. gloeosporioides requires copper at the initial stages of pathogenesis and germination, and potassium for maintaining cell shape, membrane potential, intracellular pH, and enzyme activity (Barhoom et al, 2008; Pan et al, 2022).…”
Section: Identification and Pathogenicity Of Colletotrichum Spp In Te...mentioning
confidence: 99%